Advances in Polymer Science
DOI: 10.1007/12_062
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Approaches to Neutral and Charged Polymer Brushes

Abstract: Neutral or charged polymers that are densely end-grafted to surfaces form brushlike structures and are highly stretched under good-solvent conditions. We discuss and compare relevant results from scaling models, self-consistent-field methods and MD simulation techniques and concentrate on the conceptual simple case of planar substrates. For neutral polymers the main quantity of interest is the brush height and the polymer density profile, which can be well predicted from self-consistent calculations and simula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 105 publications
6
71
0
Order By: Relevance
“…This regime of a polyelectrolyte brush is known as the osmotic regime in which some theoretical scaling methods predict no dependence of the brush thickness to the grafting density [18,29]. However, other scaling method that takes into account the excluded volume effects and nonlinear elasticity of polyelectrolyte chains predicts a linear dependence of the brush thickness on the grafting density and is in agreement with experiment and simulation [23,24,25]. Also, it has been shown that diffusion of a fraction of counterions outside the polyelectrolyte brush leads to a logarithmic dependence of the average brush thickness on the grafting density [22].…”
Section: Introductionsupporting
confidence: 62%
“…This regime of a polyelectrolyte brush is known as the osmotic regime in which some theoretical scaling methods predict no dependence of the brush thickness to the grafting density [18,29]. However, other scaling method that takes into account the excluded volume effects and nonlinear elasticity of polyelectrolyte chains predicts a linear dependence of the brush thickness on the grafting density and is in agreement with experiment and simulation [23,24,25]. Also, it has been shown that diffusion of a fraction of counterions outside the polyelectrolyte brush leads to a logarithmic dependence of the average brush thickness on the grafting density [22].…”
Section: Introductionsupporting
confidence: 62%
“…Under theta solvent conditions (our case), =0.5 and y = 3 [49]. The AdG scaling theory assumes a step -like density profile for the unperturbed brush and that the brushes do not interdigitate, which are known to be overly simplifying assumptions in actual polymer brushes [47,50], see Figs.…”
Section: Resultsmentioning
confidence: 99%
“…They have shown that the elastic properties of the grafted brush can be expressed in terms of an effective shear modulus, which depends on the square of the grafting density (Williams, 1993b). For a recent review of theoretical and numerical approaches to the description of polymer brushes, see Naji et al (2006).…”
Section: Introductionmentioning
confidence: 98%